2020
DOI: 10.1186/s13041-020-00677-3
|View full text |Cite
|
Sign up to set email alerts
|

α2-Antiplasmin as a potential regulator of the spatial memory process and age-related cognitive decline

Abstract: α2-Antiplasmin (α2AP), a principal physiological plasmin inhibitor, is mainly produced by the liver and kidneys, but it is also expressed in several parts of the brain, including the hippocampus and cerebral cortex. Our previous study demonstrated that α2AP knockout mice exhibit spatial memory impairment in comparison to wild-type mice, suggesting that α2AP is necessary for the fetal and/or neonatal development of the neural network for spatial memory. However, it is still unclear whether α2AP plays a role in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 43 publications
(55 reference statements)
0
2
0
Order By: Relevance
“…Consequently, fibrin degrades and blood components can enter the brain, leading to inflammation and nerve cell damage. Studies using mouse models of AD have shown that suppression of A2AP expression increases plasmin activity, resulting in enhanced Aβ deposition and inflammation in the brain [37,38].…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, fibrin degrades and blood components can enter the brain, leading to inflammation and nerve cell damage. Studies using mouse models of AD have shown that suppression of A2AP expression increases plasmin activity, resulting in enhanced Aβ deposition and inflammation in the brain [37,38].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, profibrotic factors including CTGF, HMGB1 and IFN-γ induce α2AP production in fibroblasts [ 11 , 38 , 66 ], and the increase in α2AP expression may affect fibrosis progression in SSc. Furthermore, it has been reported that α2AP deficiency attenuates oxidative stress [ 117 ] and promotes apoptosis [ 17 ], and α2AP may affect the induction of oxidative stress and resistance to apoptosis in SSc. On the other hand, plasmin can activate MMPs, such as MMP-1, MMP-3, and MMP-9, and degrade ECM [ 118 , 119 , 120 ].…”
Section: α2ap and Fibrosis In Sscmentioning
confidence: 99%
“…In addition, the α2AP neutralizing antibody enhances fibrinolysis and thrombus dissolution [ 23 , 25 , 147 ]. Furthermore, α2AP deficiency attenuates oxidative stress [ 117 ], and α2AP neutralization may attenuate oxidative stress in SSc.…”
Section: The Role Of α2ap As a Therapeutic Target For Sscmentioning
confidence: 99%